Food or food: outlining the edges of the city through gastronomic guides - Santos, Tassi de Oliveira (2024)
The act of eating transcends mere hunger satiation. Cooking becomes history and language within the societies it is present. Focusing on the city of São Paulo immerses us in a narrative of gastronomic territories that are unevenly explored. The affluent axes are constantly highlighted, leaving at the margins those that exceed the geographic boundaries of the city center. In this context, gastronomic guides play a crucial role: which story should be prioritized in the selection of our references? Thus, conceived from a political perspective of valuing "real food", the one that is “good and affordable”, emerges the Prato Firmeza. It features gastronomic enterprises that extend beyond the city center of São Paulo, reaching the periphery and its inhabitants. The objective is to analyze the sociocultural representativeness expressed by gastronomic guides through a comparison between Prato Firmeza and the Michelin Guide. The article presents a qualitative, exploratory, and descriptive approach, based on bibliographic and documentary research. Among the main findings is the importance of the Prato Firmeza guide as an element of resistance against the cultural homogenization proposed by globalization in the context of gastronomy, translating the reality of São Paulo's periphery.